Metal Scrappers and Thieves : Scavenging for Survival and Profit - Stickle, Benjamin F. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book explores the little-known world of scrappers and metal thieves. Benjamin F. Stickle bases his study on field research collected while traversing communities with thieves and scrappers. Drawing on candid interviews, observations of criminals at work, and participation in the scrapping subculture, the volume describes the subculture of scrappers and identifies differences between scrappers and metal thieves. Through the offenders' perspective, often quoting their candid responses, Stickle explores the motivations for metal theft as well as the techniques and methods for successfully committing theft. The book discusses how these methods and techniques are learned and identifies ways-often through the thieves' own words-to prevent metal theft. Throughout the book, Stickle also challenges common assumptions about this community and identifies wider policy implications.
Keywords: Social sciences.; Ethnography.; Crime -- Sociological aspects.; Social justice.; Human rights.; elektronické knihy; electronic books